2logx+log(x+9)-log(x-9)=1

Simple and best practice solution for 2logx+log(x+9)-log(x-9)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2logx+log(x+9)-log(x-9)=1 equation:


Simplifying
2logx + log(x + 9) + -1log(x + -9) = 1

Reorder the terms:
2glox + glo(9 + x) + -1log(x + -9) = 1
2glox + (9 * glo + x * glo) + -1log(x + -9) = 1
2glox + (9glo + glox) + -1log(x + -9) = 1

Reorder the terms:
2glox + 9glo + glox + -1glo(-9 + x) = 1
2glox + 9glo + glox + (-9 * -1glo + x * -1glo) = 1
2glox + 9glo + glox + (9glo + -1glox) = 1

Reorder the terms:
9glo + 9glo + 2glox + glox + -1glox = 1

Combine like terms: 9glo + 9glo = 18glo
18glo + 2glox + glox + -1glox = 1

Combine like terms: 2glox + glox = 3glox
18glo + 3glox + -1glox = 1

Combine like terms: 3glox + -1glox = 2glox
18glo + 2glox = 1

Solving
18glo + 2glox = 1

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Reorder the terms:
-1 + 18glo + 2glox = 1 + -1

Combine like terms: 1 + -1 = 0
-1 + 18glo + 2glox = 0

The solution to this equation could not be determined.

See similar equations:

| 10y-8=2 | | 5x-2x+7-x=5x+2 | | 3(2n-3)=5(n+1) | | -3x-3(2x-14)=-66 | | 5x-2x+7-x=7x+4 | | 8.2-4.4= | | 10=-2a-8a | | 5x-2x+7-x=6x+9 | | 5x-2x+7-x=9x+8 | | 0.6w-0.3w+0.2=2 | | 2logx-log(x+9)-log(x+9)=1 | | 5x-2x+7-x=3x+6 | | -28=4x-3(5x-9) | | 6y-4y-10=17.98 | | x=20+x | | 11=m-4 | | 5x-2x+7-x=2x+9 | | 5/9/1954 | | -0.2(3x+15)=3(0.8x-8) | | 8x+(2x-3)=(8x+2x)-3 | | 4+7(-2d-5)= | | h+6.5=11.4 | | 12y-10y-14=7.08 | | 4-7(-2d-5)= | | 6(3.2y-1)=3 | | 6x+3y+z=93 | | 6(-9q+3)= | | 12+n-10=5n | | -24=6x-3(7x-22) | | 2logx-log(x+9)-log(x-9)=1 | | 37=1.5x+4 | | 4(x-3)=7+2(x+6) |

Equations solver categories